Optimization of synthesis condition and the electrochemical properties of LiVMO6−δ (M=Mo or W) as candidate positive electrode material for lithium batteries - Prabaharan, S (2002)
A new family of high voltage (4 V) class positive electrode materials namely LiVMO6-delta [M=Mo or W] has been identified for use in lithium-containing rechargeable cells. The lithiated twin transition metal oxides have been synthesized following a simple aqueous solution reaction (ASR) process called soft-combustion method. The submicronic particles of the electrode powder, thus prepared, demonstrate the high voltage behavior in lithium-containing cells, Electrochemical studies such as galvanostatic intermittent charge-discharge (GITT) experiments and cyclic voltammetry (CV) have proved that these materials could certainly be regarded as 4-V type materials with specific capacities as high as similar to 165 mA h/g (LiVMoO6-delta) and similar to 95 mA h/g ((LiVWO6-delta) between 4.6 and 2.8 V Both these materials are found to have similar electrochemical character with respect to their operating voltages. Among these brannerites, LiVMoO6-delta exhibits a higher practical capacity than its tungstate counterpart. (C) 2002 Elsevier Science B.V. All rights reserved.